Audio watermarking in partially compressed-encrypted domain - Subramanyam, A. V. (2013)
In Digital Asset Management systems, media is often handled in compressed and encrypted form. In this paper, we propose a novel partially compressed-encrypted robust MP3 audio watermarking technique. However, arbitrary embedding of a watermark in a partially compressed encrypted MP3 audio can cause drastic degradation of the quality as the underlying change may result in random decrypted values. In addition, encryption may result in very low compression efficiency. Thus the challenge is to design a watermarking technique that provides good watermarked audio quality and at the same time gives good compression efficiency. While the proposed technique embeds watermark in the partially compressed-encrypted domain, the extraction of watermark can be done in the encrypted or decrypted domains. The experiments show that the watermarked audio quality is good and the reduction in compression efficiency is low. The experimental results also show that the proposed watermarking technique is robust to common signal processing attacks.